Asymmetric Effects of U.S. Monetary Policy on the U.S. Bilateral Trade Deficit With China: A Markov Switching ARDL Model Approach - Su, Thanh Dinh (Archīum Ateneo, 2020)
This study investigates the dynamics between U.S. monetary policy and its bilateral trade deficit with China. Applying an ARDL version plugged into the Markov switching model to the U.S. quarterly time series data over the 1993Q1–2018Q3 period, the results show that the U.S. trade deficit with China exists in two regimes, namely regime 1 with a low trade balance and regime 2 with a high trade balance. Notably, the effects of U.S. monetary policy are asymmetric on the trade balance between the two regimes, and they are convergent in the long run. U.S. monetary policy, in return, is also affected by China’s monetary policy.